Management of Cholelithiasis with Concomitant Choledocholithiasis - Ardhitio Musthafa Akmal; Budhiarko Pramana Putra; Cokorda Istri Agung Asvini Darmaningrat; I Gusti Ayu Ratih Chantika Nariswari; Lalu Dio Srigede; Catarina Budyono (Interna Publishing, 2022)
Cholelithiasis refers to a condition in which hardened deposits exist within the gall bladder. These deposits are also known as gallstones. Among other gastrointestinal diseases, Cholelithiasis is associated with the highest hospital admissions. Those with cholelithiasis are generally asymptomatic. However, symptoms may start to appear in the case of inflammation or the blockage of the bile duct, which occurs in 10-25% of patients with cholelithiasis. The condition in which gallstones are present in the common bile duct is known as choledocholithiasis. Surgery is a curative therapy for cholelithiasis concomitant with choledocholithiasis. Other available options include laparoscopy, endoscopy, percutaneous technique, and open surgery. These methods can be done gradually or in combination. Considering this, there have been controversies about the best management option for the case. Therefore, this article aims to analyze and compare each methods of management.